PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASIONAL (Studi Kasus Di SMA Negeri 1 Jakenan Kabupaten Pati) - Markonah, Siti; ., Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2016)
This research purposed to examine motivation influence teacherâs competence about the job of SMAN 1 Jakenan teacher be mediated by organizational commitment.The spesific purpose of this research is to examine organizational commitment role in job motivation influence and teacher competence through the teacherâs work.The useful of this research is to explaint and enlarge the reseach before about organizational commitment role mediated job motivation influence and teacherâs competence about the teacherâs work.This research use the sum of SMA N 1 Jakenan teachers in Pati regency about 70 teachers.The sample removal technic in this reseach is by census technic,its mean that we use all of the sample. According to the reseach, we can conclude that: job motivation have positivs influence and significant to organizational commitment,teacher competence have positive influence and significant to organizational commitment, job motivation donât have influence to teacheâr work, teacher competence have positive influence and significant to techerâs work, organizational commitment mediation effec of motivation of the teacherâs work, organizational commitment doesnot mediate to the effect of teacher competence of the teacherâs work. Key word : job motivation, teacher competence, organizational commitment and teacherâs work